Solve x^2=4(x-3)^2

expand the brackets to obtain x^2=4(x^2-6x+9)expand the brackets to obtain x^2=4x^2-24x+36rearrange to obtain 0=3x^2-24x+36factorise to obtain 0=(3x-6)(x-6)solve for x=6 or x=2

Answered by Edwin E. Maths tutor

2704 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

How does one find the area of a generic triangle?


Given that dx/dt = (1+2x)*4e^(-2t) and x = 1/2 when t = 0, show that ln[2/(1+2x)] = 8[1 - e^(-2t)]


Integrate the following equation to find y: dy/dx = 3x^2 + 2x + 6


Use integration by parts to find the value of definite integral between 5 and 1 (3x/root(2x-1))dx


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences